Secondary battery and electronic device
Patent Information
- Application Number
- CN202410254699.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-06
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-03-06
AI Technical Summary
[0003]通常,为了减少电解液与正极极片、电解液与负极极片之间的界面副反应,会在正极极片和负极极片之间设置具有较高粘结力的隔离膜,但会造成电解液的存储空间减少,容易导致因电解液浸润不足引起的循环性能衰减问题
[0026] This application provides a secondary battery and an electronic device. The secondary battery includes a positive electrode, a negative electrode, a separator, and an electrolyte. The electrolyte includes a compound represented by Formula I, R. 11 and R 12 Each is independently selected from C1 to C6 alkyl groups, whether halogenated or unsubstituted, and R 11 or R 12At least one of the components is replaced by a halogen; based on the mass of the electrolyte, the mass percentage of the compound represented by Formula I is A%, 30≤A≤80; the separator includes a porous substrate layer and an adhesive layer disposed on two surfaces of the porous substrate layer, the adhesive layer comprising a polymer, the adhesion force between the separator and the positive electrode is F1 N/m, 10≤F1≤15; the adhesion force between the separator and the negative electrode is F2 N/m, 18≤F2≤25. The separator of this application has high adhesion force between the positive electrode and the negative electrode, which easily leads to problems such as cycle performance degradation due to electrolyte deficiency and high expansion rate during cycling. The electrolyte, comprising the compound shown in Formula I and with the value of A controlled within the aforementioned range, can improve the antioxidant properties of the electrolyte, reduce interfacial side reactions between the positive electrode and the electrolyte, and between the negative electrode and the electrolyte, thus reducing electrolyte consumption and slowing down the electrolyte loss rate, thereby improving the cycle performance of the secondary battery. Simultaneously, the electrolyte, comprising the compound shown in Formula I and with the value of A controlled within the aforementioned range, can improve the interfacial stability between the positive electrode and the electrolyte, further reducing electrolyte consumption and slowing down the electrolyte loss rate. It can also reduce oxygen release from the positive electrode active material, mitigating the electrode expansion problem caused by the accumulation of byproducts from electrolyte decomposition during cycling, thereby improving both the cycle performance and expansion performance of the secondary battery.
Smart Images

Figure BDA0004729852540000011 
Figure BDA0004729852540000021 
Figure BDA0004729852540000031
Abstract
Description
Technical Field
[0001] This application relates to the field of electrochemical technology, and in particular to a secondary battery and electronic device. Background Technology
[0002] Secondary batteries, such as lithium-ion batteries, are widely used in smartphones, wearable devices, consumer drones, and electric vehicles due to their advantages such as high energy density, long cycle life, and no memory effect.
[0003] Typically, in order to reduce interfacial side reactions between the electrolyte and the positive electrode, or between the electrolyte and the negative electrode, a separator with high adhesion is placed between the positive and negative electrodes. However, this reduces the electrolyte storage space and can easily lead to cycle performance degradation due to insufficient electrolyte wetting. Summary of the Invention
[0004] The purpose of this application is to provide a secondary battery and electronic device to improve the cycle performance of the secondary battery. The specific technical solution is as follows:
[0005] A first aspect of this application provides a secondary battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the electrolyte comprises a compound represented by Formula I.
[0006]
[0007] R 11 and R 12 Each is independently selected from C1 to C6 alkyl groups, whether halogenated or unsubstituted, and R 11 or R 12At least one of the components is replaced by a halogen; based on the mass of the electrolyte, the mass percentage of the compound represented by Formula I is A%, 30≤A≤80; the separator includes a porous substrate layer and an adhesive layer disposed on two surfaces of the porous substrate layer, the adhesive layer comprising a polymer, the adhesion force between the separator and the positive electrode is F1 N / m, 10≤F1≤15; the adhesion force between the separator and the negative electrode is F2 N / m, 18≤F2≤25. The separator of this application has high adhesion force between the positive electrode and the negative electrode, resulting in reduced electrolyte storage space, which can easily lead to problems such as decreased cycle performance due to electrolyte deficiency and high expansion rate during cycling. The electrolyte, comprising the compound shown in Formula I and with the value of A controlled within the aforementioned range, can improve the antioxidant properties of the electrolyte, reduce interfacial side reactions between the positive electrode and the electrolyte, and between the negative electrode and the electrolyte, thus reducing electrolyte consumption and slowing down the electrolyte loss rate, thereby improving the cycle performance of the secondary battery. Simultaneously, the electrolyte, comprising the compound shown in Formula I and with the value of A controlled within the aforementioned range, can improve the interfacial stability between the positive electrode and the electrolyte, further reducing electrolyte consumption and slowing down the electrolyte loss rate. It can also reduce oxygen release from the positive electrode active material, mitigating the electrode expansion problem caused by the accumulation of byproducts from electrolyte decomposition during cycling, thereby improving both the cycle performance and expansion performance of the secondary battery.
[0008] In some embodiments of this application, the secondary battery satisfies at least one of the following characteristics: (1) R 11 or R 12 (1) At least one of the components is replaced by F; (2) 40≤A≤75. Secondary batteries that meet the above characteristics are more conducive to the role of the compound shown in Formula I, reducing electrolyte consumption and delaying the electrolyte loss rate, thereby further improving the cycle performance and expansion performance of secondary batteries.
[0009] In some embodiments of this application, the compound represented by Formula I includes at least one of the following compounds:
[0010]
[0011]
[0012] The electrolyte includes compounds of Formula I within the above-mentioned range, which can better exert the function of compounds of Formula I, reduce electrolyte consumption, and slow down the electrolyte loss rate, thereby improving the cycle performance and expansion performance of secondary batteries.
[0013] In some embodiments of this application, the electrolyte further includes a non-substituted carboxylic acid ester compound, which includes at least one selected from methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, or propyl propionate. Based on the mass of the electrolyte, the mass percentage of the non-substituted carboxylic acid ester compound is B%, with 10 ≤ B ≤ 50. Further introducing the aforementioned non-substituted carboxylic acid ester compound into the electrolyte and controlling its mass percentage B% within the above range is beneficial for further reducing the viscosity of the electrolyte, improving the wettability of the electrolyte to the positive and negative electrode plates, and allowing nearby electrolyte to quickly replenish the missing portion when local electrolyte loss occurs. This helps reduce electrolyte consumption, slows down the electrolyte loss rate, and thus improves the cycle performance and expansion performance of the secondary battery.
[0014] In some embodiments of this application, 1 ≤ A / B ≤ 7. By adjusting the value of A / B within the above range, the compound represented by Formula I in the electrolyte can synergistically work with the non-substituted carboxylic acid ester compound, which is beneficial for reducing the viscosity of the electrolyte, improving the wettability of the electrolyte to the positive and negative electrode plates, and allowing the nearby electrolyte to quickly replenish the missing portion when there is a local electrolyte deficiency. This helps reduce electrolyte consumption and slow down the electrolyte loss rate, thereby improving the cycle performance and expansion performance of the secondary battery.
[0015] In some embodiments of this application, the secondary battery satisfies at least one of the following characteristics: (1) the area ratio of the orthographic projection of the adhesive layer on the surface of the porous substrate layer is 15% to 85%; (2) the average particle size of the polymer particles is 0.2 μm to 2 μm. The secondary battery satisfying these characteristics enables greater adhesion between the separator and the positive electrode, and between the separator and the negative electrode, thereby improving the cycle performance and expansion performance of the secondary battery.
[0016] In some embodiments of this application, the secondary battery satisfies at least one of the following characteristics: (1) the area ratio of the orthographic projection of the adhesive layer on the surface of the porous substrate layer is 30% to 70%; (2) the average particle size of the polymer particles is 0.3 μm to 1 μm; (3) the weight-average molecular weight of the polymer is 300,000 to 3,000,000. The secondary battery satisfying these characteristics further enhances the adhesion between the separator and the positive electrode, and between the separator and the negative electrode, thereby improving the cycle performance and expansion performance of the secondary battery.
[0017] In some embodiments of this application, the polymer includes non-core-shell polymers or core-shell polymers. Non-core-shell polymers include at least one selected from polyvinylidene fluoride (PVDF), PVDF-HFP copolymer, styrene-butadiene copolymer, polyacrylonitrile, butadiene-acrylonitrile copolymer, polyacrylic acid, polyacrylate, or acrylate-styrene copolymer. The core of the core-shell polymer includes at least one selected from PVDF, polyacrylate, or acrylate-acrylonitrile copolymer, and the shell of the core-shell polymer includes at least one selected from PVDF-HFP copolymer, styrene-acrylate copolymer, or acrylic acid-acrylate copolymer. The polymers satisfying these characteristics enable greater adhesion between the separator and the positive electrode, and between the separator and the negative electrode, thereby improving the cycle performance and expansion performance of the secondary battery.
[0018] In some embodiments of this application, the electrolyte further includes ethylene carbonate and propylene carbonate, wherein the mass percentage of ethylene carbonate is D% and the mass percentage of propylene carbonate is E%, based on the mass of the electrolyte, 0≤D+E≤10, 0≤D≤10. Further introducing ethylene carbonate and / or propylene carbonate into the electrolyte and controlling the values of D+E and D within the aforementioned ranges can further enhance the dissociation of lithium salts by the compounds shown in Formula I, increase the conductivity of the electrolyte, and help reduce the polarization of the secondary battery. It also facilitates the formation of lithium salt anions at the positive or negative electrode interface, forming an inorganic-rich positive electrode electrolyte interface (CEI) film or negative electrode electrolyte interface (SEI) film, enhancing the interfacial stability between the positive electrode and the electrolyte, and between the negative electrode and the electrolyte, thereby improving the cycle performance and expansion performance of the secondary battery.
[0019] In some embodiments of this application, 0 ≤ E ≤ 10. By adjusting the value of E within the above range, it is beneficial for the dissociation of lithium salt in the electrolyte, increasing the conductivity of the electrolyte, reducing the polarization of the secondary battery, and also facilitating the formation of lithium salt anions at the positive or negative electrode interface to form an inorganic-rich CEI or SEI film. This enhances the interfacial stability between the positive electrode and the electrolyte, and between the negative electrode and the electrolyte, thereby improving the cycle performance and expansion performance of the secondary battery.
[0020] In some embodiments of this application, the electrolyte further includes a fluorocyclic carbonate, wherein the mass percentage of the fluorocyclic carbonate is F%, based on the mass of the electrolyte, 1 ≤ F ≤ 20, and the fluorocyclic carbonate includes at least one of the following compounds:
[0021]
[0022] By further introducing fluorinated cyclic carbonates into the electrolyte and adjusting the value of F within the above range, it can synergistically interact with the compound shown in Formula I to improve the interfacial stability between the positive electrode and the electrolyte, and between the negative electrode and the electrolyte. This helps to reduce electrolyte consumption and slow down the electrolyte loss rate, thereby improving the cycle performance and expansion performance of the secondary battery.
[0023] In some embodiments of this application, 3 ≤ F ≤ 10. By adjusting the value of F within the above range, it is more beneficial to exert the effect of fluorinated cyclic carbonates, thereby further improving the cycle performance and expansion performance of the secondary battery.
[0024] The second aspect of this application provides an electronic device that includes the secondary battery provided in the first aspect of this application. The secondary battery provided in this application has good cycle performance and expansion performance, thereby providing the electronic device with a long service life and good performance.
[0025] The beneficial effects of this application are:
[0026] This application provides a secondary battery and an electronic device. The secondary battery includes a positive electrode, a negative electrode, a separator, and an electrolyte. The electrolyte includes a compound represented by Formula I, R. 11 and R 12 Each is independently selected from C1 to C6 alkyl groups, whether halogenated or unsubstituted, and R 11 or R 12At least one of the components is replaced by a halogen; based on the mass of the electrolyte, the mass percentage of the compound represented by Formula I is A%, 30≤A≤80; the separator includes a porous substrate layer and an adhesive layer disposed on two surfaces of the porous substrate layer, the adhesive layer comprising a polymer, the adhesion force between the separator and the positive electrode is F1 N / m, 10≤F1≤15; the adhesion force between the separator and the negative electrode is F2 N / m, 18≤F2≤25. The separator of this application has high adhesion force between the positive electrode and the negative electrode, which easily leads to problems such as cycle performance degradation due to electrolyte deficiency and high expansion rate during cycling. The electrolyte, comprising the compound shown in Formula I and with the value of A controlled within the aforementioned range, can improve the antioxidant properties of the electrolyte, reduce interfacial side reactions between the positive electrode and the electrolyte, and between the negative electrode and the electrolyte, thus reducing electrolyte consumption and slowing down the electrolyte loss rate, thereby improving the cycle performance of the secondary battery. Simultaneously, the electrolyte, comprising the compound shown in Formula I and with the value of A controlled within the aforementioned range, can improve the interfacial stability between the positive electrode and the electrolyte, further reducing electrolyte consumption and slowing down the electrolyte loss rate. It can also reduce oxygen release from the positive electrode active material, mitigating the electrode expansion problem caused by the accumulation of byproducts from electrolyte decomposition during cycling, thereby improving both the cycle performance and expansion performance of the secondary battery.
[0027] Of course, implementing any product or method of this application does not necessarily require achieving all of the advantages described above at the same time. Detailed Implementation
[0028] The technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. All other embodiments obtained by those skilled in the art based on this application are within the scope of protection of this application.
[0029] It should be noted that, in the following explanation, lithium-ion batteries are used as an example of secondary batteries to illustrate this application; however, the secondary batteries in this application are not limited to lithium-ion batteries. The specific technical solution is as follows:
[0030] A first aspect of this application provides a secondary battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the electrolyte comprises a compound represented by Formula I.
[0031]
[0032] R 11 and R 12 Each is independently selected from C1 to C6 alkyl groups, whether halogenated or unsubstituted, and R 11 or R12 At least one of the components is replaced by a halogen, including F, Cl, Br, I, preferably R. 11 or R 12 At least one of them is replaced by F. In some embodiments of this application, R 11 and R 12 Each group is independently selected from the following groups, whether halogen-substituted or unsubstituted: methyl, ethyl, or propyl, R 11 or R 12 At least one of the components is replaced by a halogen. Based on the mass of the electrolyte, the mass percentage of the compound represented by Formula I is A%, 30 ≤ A ≤ 80, preferably 40 ≤ A ≤ 75. For example, the value of A can be 30, 35, 40, 43, 46, 48, 50, 52, 55, 58, 60, 62, 64, 67, 70, 73, 75, 80, or a range of any two of these values. The separator includes a porous substrate layer and adhesive layers disposed on two surfaces of the porous substrate layer. The adhesive layers include a polymer. The adhesion force between the separator and the positive electrode is F1 N / m, 10 ≤ F1 ≤ 15; the adhesion force between the separator and the negative electrode is F2 N / m, 18 ≤ F2 ≤ 25. For example, the value of F1 can be 10, 11, 12, 13, 14, 15, or a range of any two of these values. The value of F2 can be 18, 19, 20, 21, 22, 23, 24, 25, or a range of any two of these values.
[0033] The separator in this application exhibits high adhesion to both the positive and negative electrode plates, resulting in reduced electrolyte storage space. This can easily lead to problems such as decreased cycle performance due to electrolyte loss and high expansion rate during cycling. The electrolyte, comprising the compound shown in Formula I and with the value of A controlled within the aforementioned range, can improve the electrolyte's antioxidant properties, reduce interfacial side reactions between the positive and negative electrode plates and the electrolyte, thus reducing electrolyte consumption and slowing down the electrolyte loss rate, thereby improving the cycle performance of the secondary battery. Simultaneously, the electrolyte, comprising the compound shown in Formula I and with the value of A controlled within the aforementioned range, can improve the interfacial stability between the positive and negative electrode plates, further reducing electrolyte consumption and slowing down the electrolyte loss rate. It can also reduce oxygen release in the positive electrode active material, mitigating the electrode (including both positive and negative electrode plates) expansion problem caused by the accumulation of byproducts from electrolyte decomposition during cycling. Therefore, it improves both the cycle performance and expansion performance of the secondary battery. When the value of F1 is too small, for example, less than 10, the adhesion between the separator and the positive electrode is weak. This weak interfacial contact easily leads to a positive electrode "break-bridge," causing the separator and the positive electrode to lose contact, thus affecting ion transport between them. Similarly, when the value of F2 is too small, for example, less than 18, the adhesion between the separator and the negative electrode is weak. This weak interfacial contact easily leads to a negative electrode "break-bridge," causing the separator and the negative electrode to lose contact, thus affecting ion transport between them. Therefore, when the values of F1 and / or F2 are too small, it is detrimental to improving the cycle performance and expansion performance of the secondary battery. When the value of F1 is too large, for example, greater than 15, the electrolyte is insufficient to fully wet the positive electrode. When the value of F2 is too large, for example, greater than 25, the electrolyte is insufficient to fully wet the negative electrode. Therefore, when the values of F1 and / or F2 are too large, it is also detrimental to improving the cycle performance and expansion performance of the secondary battery. When A is too small, for example, less than 30%, the mass percentage of the compound shown in Formula I is too low, limiting its effectiveness. Its ability to reduce electrolyte consumption and slow electrolyte loss is weak, failing to improve the cycle performance and expansion performance of the secondary battery. When A is too large, for example, greater than 80%, the mass percentage of the compound shown in Formula I is too high, leading to a sharp increase in electrolyte viscosity. This increases concentration polarization in the secondary battery, increasing its impedance and further hindering improvement in cycle performance and expansion performance. Therefore, by controlling the adhesion force F1 between the separator and the positive electrode and the adhesion force F2 between the separator and the negative electrode within the scope of this application, and by adding the compound shown in Formula I to the electrolyte, with the mass percentage A% of the compound shown in Formula I within the scope of this application, the cycle performance and expansion performance of the secondary battery can be improved.
[0034] In some embodiments of this application, the compound represented by Formula I includes at least one of the following compounds:
[0035]
[0036] The electrolyte includes compounds of Formula I within the aforementioned range, which can better leverage the effects of the compounds of Formula I, improve the antioxidant properties of the electrolyte, reduce interfacial side reactions between the positive electrode and the electrolyte, and between the negative electrode and the electrolyte, and also improve the interfacial stability between the positive electrode and the electrolyte. This helps to reduce electrolyte consumption, slow down the electrolyte loss rate, reduce oxygen release in the positive electrode active material, and improve the electrode expansion problem caused by the accumulation of byproducts generated by electrolyte decomposition during the cycle, thereby improving the cycle performance and expansion performance of the secondary battery.
[0037] In some embodiments of this application, the electrolyte further includes a non-substituted carboxylic acid ester compound, which includes at least one selected from methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, or propyl propionate. The mass percentage of the non-substituted carboxylic acid ester compound is B%, based on the mass of the electrolyte, with 10 ≤ B ≤ 50. For example, the value of B can be 10, 16, 20, 25, 30, 36, 40, 44, 50, or a range of any two of these values. Further introducing the aforementioned non-substituted carboxylic acid ester compound into the electrolyte and controlling its mass percentage B% within the above range is beneficial because the compound shown in Formula I has a high viscosity. The non-substituted carboxylic acid ester compound has a similar structure to the compound shown in Formula I, good affinity, and low viscosity. This is conducive to further reducing the viscosity of the electrolyte, improving the wettability of the electrolyte to the positive and negative electrode plates, and allowing the nearby electrolyte to quickly replenish the missing electrolyte when there is a local electrolyte deficiency. This helps to reduce electrolyte consumption, slow down the electrolyte loss rate, and thus improve the cycle performance and expansion performance of the secondary battery.
[0038] In some embodiments of this application, 1 ≤ A / B ≤ 7. For example, the value of A / B can be 1, 1.4, 2, 2.5, 3, 3.6, 4, 4.4, 5, 5.3, 6, 6.5, 7, or a range of any two of these values. By adjusting the value of A / B within the above range, the compound represented by Formula I in the electrolyte can synergistically interact with the non-substituted carboxylic acid ester compound, which is beneficial for reducing the viscosity of the electrolyte, improving the wettability of the electrolyte to the positive and negative electrode plates, and allowing the nearby electrolyte to quickly replenish the missing portion when there is a local electrolyte deficiency. This helps reduce electrolyte consumption, slows down the electrolyte loss rate, and thus improves the cycle performance and expansion performance of the secondary battery.
[0039] In some embodiments of this application, the area ratio of the orthographic projection of the adhesive layer on the surface of the porous substrate layer is 15% to 85%, preferably 30% to 70%. For example, the area ratio of the orthographic projection of the adhesive layer on the surface of the porous substrate layer can be 15%, 20%, 30%, 35%, 40%, 44%, 50%, 56%, 60%, 65%, 70%, 80%, 85%, or any combination of two of these values. By adjusting the area ratio of the orthographic projection of the adhesive layer on the surface of the porous substrate layer within the above range, a greater adhesion force can be achieved between the separator and the positive electrode, and between the separator and the negative electrode, thereby improving the cycle performance and expansion performance of the secondary battery.
[0040] In some embodiments of this application, the average particle size of the polymer particles is from 0.2 μm to 2 μm, preferably from 0.3 μm to 1 μm. For example, the average particle size of the polymer particles can be 0.2 μm, 0.3 μm, 0.4 μm, 0.6 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, or a range consisting of any two of these values. By controlling the average particle size of the polymer particles within the above range, it is beneficial for the electrolyte to wet the polymer particles in the separator adhesive layer, resulting in greater adhesion between the separator and the positive electrode, and greater adhesion between the separator and the negative electrode, thereby improving the cycle performance and expansion performance of the secondary battery.
[0041] Typically, polymer particles with different average particle sizes can be obtained through mechanical crushing (e.g., ball milling). For example, the average particle size of the polymer can be controlled by adjusting the ball milling time. When other conditions remain constant, extending the ball milling time decreases the average particle size of the polymer; conversely, shortening the ball milling time increases the average particle size of the polymer.
[0042] In some embodiments of this application, the polymer includes a non-core-shell polymer, which includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, styrene-butadiene copolymer, polyacrylonitrile, butadiene-acrylonitrile copolymer, polyacrylic acid, polyacrylate, or acrylate-styrene copolymer. Using polymers of the above types for the separator enables greater adhesion between the separator and the positive electrode, and between the separator and the negative electrode, thereby improving the cycle performance and expansion performance of the secondary battery.
[0043] In some embodiments of this application, the polymer includes a core-shell structured polymer. The core polymer of the core-shell structured polymer includes at least one of polyvinylidene fluoride, polyacrylate, or acrylate-acrylonitrile copolymer, and the shell polymer includes at least one of polyvinylidene fluoride-hexafluoropropylene copolymer, styrene-acrylate copolymer, or acrylic acid-acrylate copolymer. This application does not impose any particular limitation on the mass ratio of the core to the shell of the core-shell structured polymer, as long as the purpose of this application is achieved. For example, the mass ratio of the core to the shell can be 1:5 to 5:1. In the above-mentioned core-shell structured polymer, the outer shell is a polymer with high adhesion, and the core is a polymer with electrolyte affinity. Using such polymers for the separator can improve the wettability of the separator by the electrolyte, while also reducing the risk of decreased adhesion of the separator due to the high swelling degree of the polymer in the electrolyte. This results in greater adhesion between the separator and the positive electrode, and greater adhesion between the separator and the negative electrode, thereby improving the cycle performance and expansion performance of the secondary battery.
[0044] In some embodiments of this application, the weight-average molecular weight of the polymer is between 300,000 and 3,000,000. For example, the weight-average molecular weight of the polymer can be 300,000, 500,000, 1,000,000, 1,400,000, 1,500,000, 1,700,000, 2,000,000, 2,300,000, 2,500,000, 2,600,000, or a range consisting of any two of these values. Controlling the weight-average molecular weight of the polymer in the separator within the above range allows for appropriate control of the polymer's swelling degree in the electrolyte, resulting in stronger adhesion between the separator and the positive electrode, and between the separator and the negative electrode, thereby improving the cycle performance and expansion performance of the secondary battery. In this application, polymers with different weight-average molecular weights can be obtained directly through purchase.
[0045] In this application, the adhesive layer also includes a dispersant. Based on the mass of the adhesive layer, the polymer content can be from 85% to 99.5% by mass, and the dispersant content can be from 0.5% to 15% by mass. This application does not impose any particular limitation on the type of dispersant, as long as it achieves the purpose of this application. For example, the dispersant may include, but is not limited to, at least one of sodium carboxymethyl cellulose or fluoroether (F2O).
[0046] In this application, the adhesive layer on the side of the separator closer to the positive electrode is defined as the first adhesive layer, and the adhesive layer on the side of the separator closer to the negative electrode is defined as the second adhesive layer. The surface density of the first and second adhesive layers can each independently be 0.01 mg / cm³. 2 Up to 0.2 mg / cm 2The thicknesses of the first and second adhesive layers can each independently range from 0.01 μm to 1 μm. This application does not impose any particular limitation on the method for preparing the adhesive layers, as long as it achieves the purpose of this application. For example, screen printing can be used to prepare the adhesive layers. This application does not impose any particular limitation on the process parameters for preparing the adhesive layers; those skilled in the art can select them according to actual needs, as long as the purpose of this application is achieved.
[0047] Typically, F1 and F2 can be controlled by adjusting the coating surface density and thickness of the first and second adhesive layers of the release liner. For example, when other conditions remain constant, increasing the coating surface density of the first adhesive layer increases F1; decreasing the coating surface density of the first adhesive layer decreases F1. Similarly, when other conditions remain constant, increasing the thickness of the first adhesive layer increases F1; decreasing the thickness of the first adhesive layer decreases F1. Likewise, when other conditions remain constant, increasing the coating surface density of the second adhesive layer increases F2; decreasing the coating surface density of the second adhesive layer decreases F2. Finally, when other conditions remain constant, increasing the thickness of the second adhesive layer increases F2; decreasing the thickness of the second adhesive layer decreases F2.
[0048] Typically, the area ratio of the adhesive layer's orthographic projection on the porous substrate surface can be controlled by changing the coating amount of the adhesive layer, thereby altering the coating area. When other conditions remain constant, increasing the coating amount increases the coating area and thus the proportion of the adhesive layer's orthographic projection on the porous substrate surface; conversely, decreasing the coating amount decreases the coating area and thus the proportion of the adhesive layer's orthographic projection on the porous substrate surface. In this application, the first and second adhesive layers have the same orthographic projection area ratio on the porous substrate surface, which is the same as the proportion of the adhesive layer's orthographic projection on the porous substrate surface.
[0049] In some embodiments, the separator further includes a heat-resistant layer disposed between the porous substrate layer and the adhesive layer. In some embodiments, the heat-resistant layer is disposed on one side of the porous substrate layer. In other embodiments, the heat-resistant layer is disposed on both sides of the porous substrate layer. This application does not impose any particular limitation on the coating surface density of the heat-resistant layer, as long as it achieves the purpose of this application. For example, the coating surface density of the heat-resistant layer can be 0.1 mg / cm³. 2 Up to 0.7 mg / cm 2 This application does not impose any particular limitation on the thickness of the heat-resistant layer, as long as the purpose of this application is achieved. For example, the thickness of the heat-resistant layer can be from 0.5 μm to 4 μm. This application does not impose any particular limitation on the method for preparing the heat-resistant layer, as long as the purpose of this application is achieved. For example, a transfer coating method can be used to prepare the heat-resistant layer. This application does not impose any particular limitation on the process parameters for preparing the heat-resistant layer; those skilled in the art can choose according to actual needs, as long as the purpose of this application is achieved.
[0050] In some embodiments, the heat-resistant layer comprises ceramic particles and a heat-resistant layer binder. This application does not impose any particular limitation on the mass percentage of ceramic particles and the heat-resistant layer binder in the heat-resistant layer, as long as the purpose of this application is achieved. For example, based on the mass of the heat-resistant layer, the mass percentage of ceramic particles can be 60% to 90%, and the mass percentage of the heat-resistant layer binder can be 10% to 40%. This application does not impose any particular limitation on the types of ceramic particles and the heat-resistant layer binder, as long as the purpose of this application is achieved. For example, the ceramic particles may include, but are not limited to, at least one of Al2O3, boehmite, TiO2, ZnO, or MgO, and the heat-resistant layer binder may include, but is not limited to, at least one of polyimide and its derivatives, aromatic nylon and its modifications, phenolic resin, or polytetrafluoroethylene.
[0051] This application does not impose any particular limitation on the porous substrate layer of the separator, as long as it achieves the purpose of this application. For example, the material of the porous substrate layer may include, but is not limited to, at least one of polyethylene, polypropylene, polyolefin films primarily composed of polytetrafluoroethylene, polyester films (e.g., polyethylene terephthalate (PET) films), cellulose films, polyimide films, polyamide films, spandex, or aramid films. The type of the porous substrate layer may include, but is not limited to, at least one of woven films, nonwoven films (non-woven fabrics), microporous films, composite films, rolled films, or spun films. In this application, the thickness of the porous substrate layer is not particularly limited, as long as it achieves the purpose of this application; for example, the thickness of the porous substrate layer may be from 3 μm to 30 μm. In this application, the pore size of the porous substrate layer is not particularly limited, as long as it achieves the purpose of this application; for example, the pore size may be from 0.01 μm to 1 μm.
[0052] In some embodiments of this application, the electrolyte further includes ethylene carbonate and propylene carbonate, wherein the mass percentage of ethylene carbonate is D% and the mass percentage of propylene carbonate is E% based on the mass of the electrolyte, with 0 ≤ D + E ≤ 10 and 0 ≤ D ≤ 10. For example, the value of D + E can be 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, or a range of any two of these values. The value of D can be 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, or a range of any two of these values. By further introducing ethylene carbonate and / or propylene carbonate into the electrolyte of the compound shown in Formula I and adjusting the values of D+E and D within the above range, the dissociation of lithium salt by the compound shown in Formula I can be further improved, the conductivity of the electrolyte can be increased, which is beneficial to reducing the polarization of the secondary battery. It is also beneficial to form a film of lithium salt anions (e.g., PF6-) at the positive or negative electrode interface, forming an inorganic-rich CEI film or SEI film, which enhances the interfacial stability between the positive electrode and the electrolyte, and between the negative electrode and the electrolyte, thereby improving the cycle performance and expansion performance of the secondary battery.
[0053] In some embodiments of this application, 0 ≤ E ≤ 10. For example, the value of E can be 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, or a range of any two of these values. By adjusting the value of E within the above range, it is beneficial for the dissociation of lithium salt in the electrolyte, increasing the conductivity of the electrolyte, reducing the polarization of the secondary battery, and also beneficial for the formation of lithium salt anions at the positive or negative electrode interface, forming an inorganic-rich CEI film or SEI film, enhancing the interfacial stability between the positive electrode and the electrolyte, and between the negative electrode and the electrolyte, thereby improving the cycle performance and expansion performance of the secondary battery.
[0054] In some embodiments of this application, the electrolyte further includes a fluorocyclic carbonate, wherein the mass percentage of the fluorocyclic carbonate is F%, based on the mass of the electrolyte, 1 ≤ F ≤ 20, preferably 3 ≤ F ≤ 10. For example, the value of F can be 1, 3, 5, 7, 10, 12, 15, 18, 20, or a range of any two of these values. The fluorocyclic carbonate includes at least one of the following compounds:
[0055]
[0056] The compound represented by Formula I in the electrolyte can improve the interfacial stability between the positive electrode and the electrolyte. Fluorinated cyclic carbonates, with their high reduction potential, preferentially form a film at the negative electrode interface, protecting the interface, reducing side reactions between the negative electrode and the electrolyte, and improving interfacial stability. Further introducing fluorinated cyclic carbonates into the electrolyte and controlling the value of F within the aforementioned range allows for synergistic effects with the compound represented by Formula I, improving interfacial stability between the positive and negative electrodes and the electrolyte. This helps reduce electrolyte consumption and slow down the electrolyte loss rate, thereby improving the cycle performance and expansion performance of the secondary battery.
[0057] In this application, the electrolyte also includes other organic solvents. This application does not impose any particular restrictions on the types of other organic solvents, as long as they achieve the purpose of this application. For example, other organic solvents may include, but are not limited to, at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), butylene carbonate (BC), vinyl ethylene carbonate (VEC), γ-butyrolactone, decanolactone, valproic acid, caprolactone, dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolium ketone, N-methyl-2-pyrrolidone, dimethylformamide, trimethyl phosphate, triethyl phosphate, or trioctyl phosphate. The mass percentage of other organic solvents is G%, 0 ≤ G ≤ 50%, based on the mass of the electrolyte. For example, G can be 0, 10, 15, 20, 23, 25, 30, 37, 35, 40, 45, 50, or a range of any two of these values.
[0058] In this application, the electrolyte also includes lithium salt. There is no particular limitation on the type of lithium salt, as long as it achieves the purpose of this application. For example, the lithium salt may include, but is not limited to, at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalate-borate), lithium difluorooxalate-borate, or lithium difluorophosphate. Preferably, the lithium salt includes lithium hexafluorophosphate. Based on the mass of the electrolyte, the mass percentage of lithium salt is H%, 8 ≤ H ≤ 20. For example, H can be 8, 10, 12, 12.5, 14, 15, 18, 20, or a range consisting of any two of these values.
[0059] In some embodiments of this application, the electrolyte may include lithium salts, compounds of Formula I, and other organic solvents. The mass percentages of lithium salts, compounds of Formula I, and other organic solvents are as described above. Secondary batteries comprising the above-described electrolyte exhibit good cycle performance and expansion performance.
[0060] In some embodiments of this application, the electrolyte may include a lithium salt, a compound of Formula I, and optionally, at least one of other organic solvents, non-substituted carboxylic acid ester compounds, ethylene carbonate, propylene carbonate, or fluorocyclic carbonates. The mass percentages of the lithium salt, the compound of Formula I, the non-substituted carboxylic acid ester compound, ethylene carbonate, propylene carbonate, fluorocyclic carbonate, and other organic solvents are as described above. Secondary batteries comprising the above-described electrolyte exhibit good cycle performance and expansion performance.
[0061] This application does not impose any particular limitation on the positive electrode sheet, as long as the purpose of this application can be achieved. For example, the positive electrode sheet includes a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector. In this application, the positive electrode material layer can be disposed on one surface of the positive current collector along its thickness direction, or it can be disposed on two surfaces of the positive current collector along its thickness direction. It should be noted that the "surface" here can be the entire area of the positive current collector or a part of the positive current collector; this application does not impose any particular limitation, as long as the purpose of this application can be achieved.
[0062] This application does not impose any particular limitation on the positive electrode current collector, as long as it achieves the purpose of this application. For example, it may include, but is not limited to, aluminum foil, aluminum alloy foil, or composite current collectors (e.g., aluminum-carbon composite current collectors). This application does not impose any particular limitation on the thickness of the positive electrode current collector and the positive electrode material layer, as long as it achieves the purpose of this application. For example, the thickness of the positive electrode current collector may be 6 μm to 12 μm, and the thickness of the positive electrode material layer may be 30 μm to 120 μm. This application does not impose any particular limitation on the thickness of the positive electrode sheet, as long as it achieves the purpose of this application; for example, the thickness of the positive electrode sheet may be 50 μm to 250 μm.
[0063] The cathode material layer of this application includes a cathode active material, which comprises a substance capable of reversibly inserting and extracting active ions such as lithium ions. The cathode material layer can be one or more layers, and each layer in a multilayer cathode material layer can contain the same or different cathode active materials. This application does not impose any particular limitation on the cathode active material, as long as it can achieve the purpose of this application. For example, the cathode active material can include, but is not limited to, at least one of lithium nickel cobalt manganese oxide (e.g., NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium manganese iron phosphate, or lithium titanate. The chemical formula of the aforementioned lithium-rich manganese-based material is γLi2MnO3·(1-γ)LiGO2, 0<γ<1, and G is a transition metal such as nickel, cobalt, or iron.
[0064] The positive electrode material layer may further include a positive electrode conductive agent and a positive electrode binder. This application does not particularly limit the types of positive electrode conductive agents and positive electrode binders, as long as they can achieve the purpose of this application. For example, the positive electrode binder may include, but is not limited to, at least one of polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, or nylon; the positive electrode conductive agent may include, but is not limited to, at least one of carbon-based materials, metal-based materials, or conductive polymers. Exemplarily, carbon-based materials may include, at least one of natural graphite, artificial graphite, conductive carbon black (Super P), or carbon fiber; metal-based materials may include, but are not limited to, at least one of metal powder, metal fiber, copper, nickel, aluminum, or silver; and conductive polymers may include, but are not limited to, polyphenylene derivatives. This application does not impose any particular restrictions on the mass ratio of positive electrode active material, positive electrode conductive agent, and positive electrode binder in the positive electrode material layer. These ratios can be selected according to actual needs, as long as the purpose of this application can be achieved.
[0065] This application does not impose any particular limitation on the negative electrode sheet, as long as it achieves the purpose of this application. For example, the negative electrode sheet includes a negative current collector and a negative electrode material layer disposed on at least one surface of the negative current collector. In this application, the negative electrode material layer can be disposed on one surface or on two surfaces in the thickness direction of the negative current collector. It should be noted that "surface" here can be the entire area of the negative current collector or a part of the negative current collector; this application does not impose any particular limitation, as long as it achieves the purpose of this application.
[0066] This application does not impose any particular limitation on the negative electrode current collector, as long as it achieves the purpose of this application. For example, it may include, but is not limited to, copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, or composite current collectors (e.g., carbon-copper composite current collector, nickel-copper composite current collector, titanium-copper composite current collector, etc.). In this application, there are no particular limitations on the thickness of the negative electrode current collector and the negative electrode material layer, as long as it achieves the purpose of this application. For example, the thickness of the negative electrode current collector may be 6 μm to 12 μm, and the thickness of the negative electrode material layer may be 30 μm to 150 μm. In this application, there are no particular limitations on the thickness of the negative electrode sheet, as long as it achieves the purpose of this application. For example, the thickness of the negative electrode sheet may be 50 μm to 350 μm.
[0067] The negative electrode material layer of this application includes a negative electrode active material. The negative electrode material layer can be one or more layers, and each layer in a multi-layer negative electrode material layer can contain the same or different negative electrode active materials. The negative electrode active material is any substance capable of reversibly inserting and extracting active ions such as lithium ions. The negative electrode active material can include, but is not limited to, graphite, mesophase microcarbon spheres (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composites, and SiO2. x (0.5 < x < 1.6), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel-structured lithium titanate lithiation TiO2-Li4Ti5O 12 At least one of Li-Al alloy and metallic lithium.
[0068] The negative electrode material layer in this application may further include a negative electrode binder and a negative electrode conductive agent, or the negative electrode material layer may further include a negative electrode binder, a negative electrode conductive agent, or a thickener. This application does not particularly limit the types of negative electrode binders and negative electrode conductive agents, as long as they achieve the purpose of this application. For example, the negative electrode binder may include, but is not limited to, at least one of the aforementioned positive electrode binders, and the negative electrode conductive agent may include, but is not limited to, at least one of the aforementioned positive electrode conductive agents. This application does not particularly limit the types of thickeners, as long as they achieve the purpose of this application. For example, the thickener may include, but is not limited to, at least one of sodium carboxymethyl cellulose or carboxymethyl cellulose. This application does not particularly limit the mass ratio of the negative electrode active material, negative electrode conductive agent, negative electrode binder, and thickener in the negative electrode material layer; they can be selected according to actual needs, as long as the purpose of this application is achieved.
[0069] The secondary battery of this application also includes a packaging bag for containing the positive electrode, separator, negative electrode, and electrolyte, as well as other components known in the art for secondary batteries. This application does not impose any particular limitation on these other components. This application also does not impose any particular limitation on the packaging bag; it can be any packaging bag known in the art, as long as it achieves the purpose of this application. For example, an aluminum-plastic film packaging bag can be used.
[0070] This application does not impose any particular limitation on the type of secondary battery, which may include any device in which an electrochemical reaction occurs. For example, secondary batteries may include, but are not limited to: lithium metal secondary batteries, lithium-ion secondary batteries (lithium-ion batteries), sodium-ion secondary batteries (sodium-ion batteries), lithium polymer secondary batteries, and lithium-ion polymer secondary batteries.
[0071] The fabrication process of secondary batteries is well known to those skilled in the art, and this application does not impose any particular limitations. For example, it may include, but is not limited to, the following steps: stacking a separator, a positive electrode, a separator, and a negative electrode in sequence, and performing operations such as winding and folding as needed to obtain a wound electrode assembly; placing the electrode assembly in a packaging bag; injecting electrolyte into the packaging bag and sealing it to obtain a secondary battery; or stacking a separator, a positive electrode, a separator, and a negative electrode in sequence, and then fixing the four corners of the entire stacked structure with tape to obtain a stacked electrode assembly; placing the electrode assembly in a packaging bag; injecting electrolyte into the packaging bag and sealing it to obtain a secondary battery. In addition, overcurrent protection components, conductive plates, etc., may be placed in the packaging bag as needed to prevent the internal pressure of the secondary battery from rising and overcharging / discharging.
[0072] The second aspect of this application provides an electronic device that includes the secondary battery provided in the first aspect of this application. The secondary battery provided in this application has good cycle performance and expansion performance, thereby providing the electronic device with a long service life and good performance.
[0073] The electronic device described in this application is not particularly limited and can be any electronic device known in the prior art. For example, the electronic device may include, but is not limited to, laptops, pen input computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, household large-capacity batteries, and lithium-ion capacitors.
[0074] Example
[0075] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were conducted according to the methods described below. Furthermore, unless otherwise specified, "parts" and "%" are quality standards.
[0076] Test methods and equipment:
[0077] Testing the area ratio of the adhesive layer projected onto the surface of the porous substrate layer.
[0078] The area ratio of the integral area of the characteristic peaks of the porous substrate layer of the separator before and after the adhesive layer coating is measured using a reflectance infrared spectrometer (Nicolet iS10). This yields the area ratio of the orthographic projection of the adhesive layer onto the porous substrate layer surface. The area ratio of the orthographic projection of the adhesive layer onto the porous substrate layer surface = 100% - (Integrated area of characteristic peaks of the porous substrate layer after adhesive layer coating / Integrated area of characteristic peaks of the porous substrate layer before adhesive layer coating) × 100%. When a heat-resistant layer is provided between the porous substrate layer and the adhesive layer of the separator, the aforementioned integrated area of the characteristic peaks of the porous substrate layer refers to the integrated area of the characteristic peaks of the porous substrate layer after the heat-resistant layer is coated.
[0079] Testing the average particle size of polymer particles
[0080] After discharging the lithium-ion batteries of each embodiment and comparative example to 3V at 0.5C, the separator membrane was disassembled. The separator membrane was cleaned with dimethyl carbonate (DMC) and dried at 60°C. Then, the surface of the separator membrane perpendicular to its thickness direction was observed using a scanning electron microscope (SEM). The SEM magnification was 5000×, and the observation area was 11.5μm × 7.5μm. Sixteen polymer particles were randomly selected within this area, and the circumcircle diameter of each polymer particle was measured. The average circumcircle diameter of the 16 polymer particles was calculated as the average particle size of the polymer.
[0081] Test of the adhesion force F1 between the separator and the positive electrode sheet
[0082] The adhesion force F1 between the separator and the positive electrode was measured using a 180° peel test. The lithium-ion batteries in the tested examples and comparative examples were disassembled after discharge, and the negative electrode was peeled off. The separator and positive electrode were soaked in dimethyl carbonate for 20 minutes to remove the electrolyte. Then, the separator and positive electrode were cut into 54.2mm × 72.5mm samples. The separator and positive electrode were then laminated using a hot press at 85°C, 1MPa, and 85s. The laminated samples were then cut into 15mm × 54.2mm strips to obtain test strips for testing the adhesion force F1 between the separator and the positive electrode. A 15mm × 55mm double-sided adhesive tape (NITTO.NO5000NS) was attached to a steel plate, and the test strips were then attached to the double-sided adhesive tape with the test side facing down. A 15mm × 70mm paper strip is attached to one end of a test strip using double-sided tape. A 2kg roller is manually pushed across the test strip eight times to obtain the test sample. A tensile testing machine is then used. The test sample is fixed on the test table, the paper strip is folded upwards 180° and secured with clamps. The tensile testing machine then pulls the paper strip at a speed of 50mm / min until the separator on the double-sided tape separates from the positive electrode plate, ending the test and saving the test data. The adhesive force F1 between the separator and the positive electrode plate is calculated based on the tensile force and displacement during separation, expressed in N / m.
[0083] Test of adhesion force F2 between the separator and the negative electrode sheet
[0084] The adhesion force F2 between the separator and the negative electrode was measured using a 180° peel test. The lithium-ion batteries in the tested examples and comparative examples were disassembled after discharge, and the positive electrode was peeled off. The separator and negative electrode were soaked in dimethyl carbonate for 20 minutes to remove the electrolyte. Then, the separator and negative electrode were cut into 54.2 mm × 72.5 mm samples. The separator and negative electrode were then laminated together using a hot press at 85°C, 1 MPa, and 85 s. The laminated samples were then cut into 15 mm × 54.2 mm strips to obtain test strips for testing the adhesion force F2 between the separator and the negative electrode. Following the same adhesion force testing procedure, the adhesion force F2 between the separator and the negative electrode was measured, with units of N / m.
[0085] Cyclic performance testing
[0086] In a constant temperature environment of 25℃, the lithium-ion battery is charged at a constant current of 1C to 4.48V, then charged at a constant voltage of 4.48V to 0.05C, and then discharged at a constant current of 1C to 3.0V. This constitutes one charge-discharge cycle, which is the first cycle, and the discharge capacity of the first cycle is recorded. The lithium-ion battery is charged and discharged in the same manner, and the discharge capacity of each cycle is recorded until the discharge capacity of the lithium-ion battery decreases to 80% of the discharge capacity of the first cycle. The number of charge-discharge cycles is recorded as the number of cycles at 25℃.
[0087] Expansion performance test
[0088] In a constant temperature environment of 25℃, the lithium-ion battery was charged at a constant current of 1C to 4.48V, then charged at a constant voltage of 4.48V to 0.05C, and then discharged at a constant current of 1C to 3.0V. This constitutes one charge-discharge cycle. The thickness of the lithium-ion battery at this point is recorded as the initial thickness of the lithium-ion battery. After repeating the above charge-discharge cycle 1000 times, the thickness of the lithium-ion battery at this point is recorded as the thickness of the lithium-ion battery after the 1000th cycle. The 25℃ cycle expansion rate is calculated using the following formula: 25℃ cycle expansion rate = (thickness of lithium-ion battery after 1000 cycles / initial thickness of lithium-ion battery - 1) × 100%.
[0089] Example 1-1
[0090] <Preparation of Electrolyte>
[0091] In an argon-atmosphere glove box with a water content of less than 10 ppm, diethyl carbonate (DEC) was used as the base solvent. Lithium hexafluorophosphate (LiPF6) and compound I-3 (Formula I) were then added to the base solvent and mixed thoroughly to obtain the electrolyte. The electrolyte consisted of 10% lithium salt (LiPF6) by mass, 50% compound I-3 (Formula I) by mass percentage (A%), and the remainder was the base solvent.
[0092] <Preparation of the separating membrane>
[0093] (1) The porous substrate layer is made of a 9μm thick polypropylene film (provided by Celgard).
[0094] (2) Preparation of heat-resistant layer adhesive: ceramic particles aluminum oxide, heat-resistant layer adhesive butadiene-styrene polymer (weight average molecular weight Mw = 7 × 10⁻⁶) are mixed. 6The solvent and deionized water were mixed at a mass ratio of 35:10:55. Specifically: First, 30 kg of butadiene-styrene polymer and deionized water were added to a 60 L double planetary mixer and dispersed at 45 °C for 3 hours; then 16.1 kg of alumina ceramic powder was added to the mixer and dispersed at 45 °C at 500 rpm for 2 hours; then ball milling was performed using a nano-milling machine for 1.5 hours, using spherical zirconia beads with a diameter of 6 μm as the grinding media to obtain the heat-resistant coating adhesive.
[0095] (3) Preparation of the heat-resistant layer: A transfer coating method is used to coat the porous substrate layer, forming a structure with heat-resistant layers on both sides, and the coating surface density of the heat-resistant layer on both sides is consistent. Specifically: the coating speed of the heat-resistant layer is 6 m / min, and the coating surface density on one side is 0.23 mg / cm³. 2 After coating, drying is carried out in three stages, with each stage having an oven length of 3m and oven temperatures set at 50℃, 60℃, and 60℃. After drying, the thickness of the heat-resistant layer on both sides is 0.7μm.
[0096] (4) Preparation of the adhesive layer solution: The polymer powder, deionized water solvent, and fluoroether F2O dispersant were mixed at a mass ratio of 5:94.5:0.5 and added to a double planetary mixer. The mixture was stirred at 45°C for 1 hour to obtain an adhesive layer solution with a solid content of 5.5 wt%. The polymer is a core-shell structure polymer, with PVDF as the core and vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) as the shell, denoted as PVDF@PVDF-HFP. The electrolyte swelling degree of this polymer is 150%, and the average particle size and weight-average molecular weight are shown in Table 4.
[0097] (5) Preparation of the adhesive layer: The heat-resistant membrane obtained in (3) with two sides having heat-resistant layers is coated on the surface using screen printing to form an isolation membrane with a first adhesive layer and a second adhesive layer on the surface. The coating surface density of the first adhesive layer and the second adhesive layer is consistent. Specifically, the coating speed of the first adhesive layer and the second adhesive layer is 4 m / min, and the coating surface density is 0.03 mg / cm³. 2 The areas of the first and second adhesive layers projected onto the porous substrate surface are in the same proportion, which is the area ratio of the adhesive layer projected onto the porous substrate surface, as shown in Table 4. Drying is performed in three stages, with each stage having a length of 3m and set temperatures of 50℃, 60℃, and 60℃. After drying, the thickness of both the first and second adhesive layers is 0.3μm.
[0098] <Preparation of the positive electrode>
[0099] The positive electrode active material is LiCoO2, the positive electrode conductive agent is conductive carbon black (Super P), and the positive electrode binder is polyvinylidene fluoride (PVDF, Mw = 7 × 10⁻⁶). 6 The materials were mixed at a mass ratio of 97.5:1:1.5, with N-methylpyrrolidone (NMP) added as a solvent. The mixture was stirred evenly under vacuum to obtain a positive electrode slurry with a solid content of 75 wt%. The positive electrode slurry was uniformly coated onto one surface of a 10 μm thick aluminum foil current collector. The foil was then dried at 85°C and cold-pressed to obtain a positive electrode sheet with a single-sided coating thickness of 50 μm. The above steps were then repeated on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided coating. After cutting and welding positive electrode tabs, a positive electrode sheet with dimensions of 74 mm × 851 mm was obtained for later use. The compaction density of the positive electrode material layer was 4.15 g / cm³. 3 .
[0100] <Preparation of Negative Electrode Sheets>
[0101] Artificial graphite as the negative electrode active material, Super P as the negative electrode conductive agent, and carboxymethyl cellulose (CMC-Na, Mw = 7 × 10⁻⁶) as the thickener (CMC-Na, Mw = 7 × 10⁻⁶) are used. 5 ), negative electrode binder styrene-butadiene rubber (SBR, Mw = 5 × 10), 6 The materials were mixed at a mass ratio of 97.5:1:0.5:1, and then deionized water was added as a solvent. The mixture was stirred evenly under vacuum to obtain a negative electrode slurry with a solid content of 50 wt%. The negative electrode slurry was uniformly coated onto one surface of an 8 μm thick copper foil current collector. It was then dried at 85°C and cold-pressed to obtain a negative electrode sheet with a single-sided coating thickness of 60 μm. The above steps were then repeated on the other surface of the copper foil to obtain a negative electrode sheet with a double-sided coating. After cutting and welding of negative electrode tabs and nickel tabs, a negative electrode sheet with dimensions of 76 mm × 867 mm was obtained for later use. The compaction density of the negative electrode material layer was 1.75 g / cm³. 3 .
[0102] <Preparation of Lithium-ion Batteries>
[0103] The separator, positive electrode, separator, and negative electrode prepared above are stacked and wound in sequence to obtain a wound electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag, dried, and then injected with electrolyte. After vacuum sealing, standing, formation (constant current charging at 0.5℃ to 3.5V, and then constant current charging at 1C to 3.9V), capacity testing, degassing, and edge trimming, a lithium-ion battery is obtained.
[0104] Examples 1-2 to Examples 1-4
[0105] Except for the types of compounds shown in Formula I as shown in Table 1 in the <Preparation of Electrolyte> section, the rest is the same as in Examples 1-1.
[0106] Examples 1-5 to Examples 1-9
[0107] Except for the preparation of the isolation membrane, in which the coating surface density of the first adhesive layer and the second adhesive layer is adjusted to make F1 and F2 as shown in Table 1, the rest is the same as in Example 1-1.
[0108] Examples 1-10 to Examples 1-13
[0109] Except for adjusting the mass percentage A% of the compound represented by Formula I as shown in Table 1 in the <Preparation of Electrolyte> section, the rest is the same as in Example 1-1. When the mass percentage A% of the compound represented by Formula I changes, the mass percentage of the base solvent changes accordingly, while the mass percentage of the lithium salt remains unchanged.
[0110] Examples 2-1 to 2-9
[0111] Except for the addition of non-substituted carboxylic acid ester compounds as shown in Table 2 in the <Preparation of Electrolyte>, the rest is the same as in Example 1-1. When the mass percentage A% of the compound represented by Formula I and / or the mass percentage B% of the non-substituted carboxylic acid ester compound changes, the mass percentage of the base solvent changes accordingly, while the mass percentage of the lithium salt remains unchanged.
[0112] Examples 3-1 to 3-4
[0113] Except for the addition of ethylene carbonate and / or propylene carbonate as shown in Table 3 in the <Preparation of Electrolyte>, the rest is the same as in Examples 1-1. When the mass percentage of ethylene carbonate (D%) and / or the mass percentage of propylene carbonate (E%) changes, the mass percentage of the base solvent changes accordingly, while the mass percentage of lithium salt remains unchanged.
[0114] Examples 3-5 to Examples 3-10
[0115] Except for the addition of fluorocyclic carbonates as shown in Table 3 in the <Preparation of Electrolyte>, the rest is the same as in Example 1-1. When the mass percentage F% of the fluorocyclic carbonates changes, the mass percentage of the base solvent changes accordingly, while the mass percentage of the lithium salt remains unchanged.
[0116] Example 3-11
[0117] Except for the addition of ethylene carbonate, propylene carbonate, and fluorocyclic carbonate as shown in Table 3 in the <Preparation of Electrolyte>, the rest is the same as in Example 1-1, except that the mass percentage of the base solvent is changed accordingly, while the mass percentage of lithium salt remains unchanged.
[0118] Examples 3-12 to 3-13
[0119] Except for the addition of non-substituted carboxylic acid ester compounds, ethylene carbonate, and propylene carbonate as shown in Table 3 in the <Preparation of Electrolyte>, the rest is the same as in Example 1-1, except that the mass percentage of the base solvent is changed accordingly, while the mass percentage of lithium salt remains unchanged.
[0120] Examples 3-14 to 3-15
[0121] Except for the addition of non-substituted carboxylic acid ester compounds and fluorocyclic carbonates as shown in Table 3 in the <Preparation of Electrolyte>, the rest is the same as in Example 1-1, except that the mass percentage of the base solvent is changed accordingly, while the mass percentage of lithium salt remains unchanged.
[0122] Examples 3-16 to 3-17
[0123] Except for the addition of non-substituted carboxylic acid ester compounds, ethylene carbonate, propylene carbonate, and fluorocyclic carbonates as shown in Table 3 in the <Preparation of Electrolyte>, the rest is the same as in Examples 1-1, except that the mass percentage of the base solvent is changed accordingly, while the mass percentage of lithium salt remains unchanged.
[0124] Examples 4-1 to 4-4
[0125] Except for adjusting the amount of adhesive coating so that the area ratio of the orthographic projection of the adhesive layer on the surface of the porous substrate layer is as shown in Table 4, the rest is the same as in Examples 1-1.
[0126] Examples 4-5 to Examples 4-8
[0127] Except for the preparation of the isolation membrane, in which the average particle size of the polymer particles is adjusted by controlling the ball milling time as shown in Table 4, the rest is the same as in Examples 1-1.
[0128] Examples 4-9 to 4-11
[0129] Except for the polymer structure, materials, and weight-average molecular weight as shown in Table 4, everything else is the same as in Examples 1-1.
[0130] Comparative Example 1
[0131] Except for <Preparation of the Separating Membrane> where the coating surface density of the first and second adhesive layers is adjusted to make F1 and F2 as shown in Table 1, <Preparation of the Electrolyte> where no compound of Formula I is added, the mass percentage of the base solvent is changed accordingly, and the mass percentage of the lithium salt remains unchanged, the rest is the same as in Examples 1-1.
[0132] Comparative Example 2
[0133] Except for the preparation of the isolation membrane, in which the coating surface density of the first adhesive layer and the second adhesive layer is adjusted to make F1 and F2 as shown in Table 1, the rest is the same as Comparative Example 1.
[0134] Comparative Examples 3 to 4
[0135] Except for the preparation of the isolation membrane, in which the coating surface density of the first adhesive layer and the second adhesive layer is adjusted to make F1 and F2 as shown in Table 1, the rest is the same as in Example 1-1.
[0136] Comparative Example 5
[0137] Except for the preparation of the isolation membrane, in which the coating surface density of the first adhesive layer and the second adhesive layer is adjusted to make F1 and F2 as shown in Table 1, the rest is the same as Comparative Example 1.
[0138] Comparative Examples 6 to 7
[0139] Except for adjusting the mass percentage A% of the compound represented by Formula I as shown in Table 1 in the <Preparation of Electrolyte> section, the rest is the same as in Example 1-1. When the mass percentage A% of the compound represented by Formula I changes, the mass percentage of the base solvent changes accordingly, while the mass percentage of the lithium salt remains unchanged.
[0140] The preparation and performance parameters of each embodiment and comparative example are shown in Tables 1 to 4.
[0141] Table 1
[0142]
[0143]
[0144] Note: " / " in Table 1 indicates that there is no corresponding parameter.
[0145] As can be seen from Examples 1-1 to 1-13 and Comparative Examples 1 to 7, the secondary battery of this application, by adjusting the adhesion force F1 between the separator and the positive electrode and the adhesion force F2 between the separator and the negative electrode within the scope of this application, and by adding the compound shown in Formula I to the electrolyte, with the mass percentage A% of the compound shown in Formula I within the scope of this application, exhibits a larger number of cycles at 25°C and a smaller cycle expansion rate at 25°C. This indicates that the secondary battery has good cycle performance and expansion performance. The secondary batteries of Comparative Examples 1 and 2 do not contain the compound shown in Formula I in their electrolytes, and F1 and F2 are not within the scope of this application; the secondary batteries of Comparative Examples 3 and 4 do not contain F1 and F2 within the scope of this application; the secondary battery of Comparative Example 5 does not contain the compound shown in Formula I in its electrolyte; the secondary batteries of Comparative Examples 6 and 7 do not contain the compound shown in Formula I in their electrolytes at a mass percentage A% that is not within the scope of this application. The secondary batteries of Comparative Examples 1 to 7 have a smaller number of cycles at 25°C and a larger cycle expansion rate at 25°C, indicating that the cycle performance and expansion performance of the secondary batteries are worse.
[0146] The values of F1 and F2 typically affect the cycle performance and expansion performance of secondary batteries. As can be seen from Examples 1-1, 1-5 to 1-9, and Comparative Examples 1 to 4, when the values of F1 and F2 are too small, such as in Comparative Examples 1 and 3, the secondary battery has a smaller number of cycles at 25°C and a larger expansion rate at 25°C; conversely, when the values of F1 and F2 are too large, such as in Comparative Examples 2 and 4, the secondary battery has a smaller number of cycles at 25°C and a larger expansion rate at 25°C. This indicates that the cycle performance and expansion performance of the secondary battery are worse. When the values of F1 and F2 are within the range specified in this application, the secondary battery has a larger number of cycles at 25°C and a smaller expansion rate at 25°C. This indicates that the cycle performance and expansion performance of the secondary battery are good.
[0147] The mass percentage A% of the compound represented by Formula I typically affects the cycle performance and expansion performance of secondary batteries. As can be seen from Examples 1-1, 1-10 to 1-13, Comparative Examples 1 to 2, and Comparative Examples 5 to 7, when A is too small, such as in Comparative Examples 1 and 2, and Comparative Examples 5 and 6, the secondary battery has a smaller number of cycles at 25°C and a larger expansion rate at 25°C; when A is too large, such as in Comparative Example 7, the number of cycles at 25°C is smaller and the expansion rate at 25°C is larger. This indicates that the cycle performance and expansion performance of the secondary battery are worse. When the value of A is within the range of this application, the secondary battery has a larger number of cycles at 25°C and a smaller expansion rate at 25°C. This indicates that the cycle performance and expansion performance of the secondary battery are good.
[0148] The type of compound represented by Formula I typically affects the cycle performance and expansion performance of secondary batteries. As can be seen from Examples 1-1 to 1-4, when the electrolyte of the secondary battery includes the compound represented by Formula I within the scope of this application, the secondary battery exhibits a larger number of cycles at 25°C and a smaller cycle expansion rate at 25°C. This indicates that the secondary battery has good cycle performance and expansion performance.
[0149] Table 2
[0150]
[0151] Note: " / " in Table 2 indicates that there is no corresponding parameter.
[0152] The mass percentage (B%) of the non-substituted carboxylic acid ester compound typically affects the cycle performance and expansion performance of a secondary battery. As seen in Examples 1-1, 2-1, and 2-3, when the electrolyte of the secondary battery includes the compound shown in Formula I, and a non-substituted carboxylic acid ester compound is further introduced, and its mass percentage (B%) is controlled within the scope of this application, the values of F1 and F2 are larger, resulting in a higher number of cycles at 25°C and a smaller cycle expansion rate at 25°C. This indicates good cycle performance and expansion performance of the secondary battery. The inventors speculate that this is because the non-substituted carboxylic acid ester compound has a lower viscosity. Further introducing a non-substituted carboxylic acid ester compound into the electrolyte and controlling the value of B within the scope of this application can improve the problem of the high viscosity of the compound shown in Formula I, reduce the viscosity of the electrolyte, improve the wettability of the electrolyte to the positive and negative electrode plates, and allow the nearby electrolyte to quickly replenish the missing portion when there is a local electrolyte deficiency, thereby enabling the secondary battery to have good cycle performance and expansion performance.
[0153] The type of non-substituted carboxylic acid ester compound typically affects the cycle performance and expansion performance of a secondary battery. As can be seen from Examples 1-1, 2-2, and 2-4, when non-substituted carboxylic acid ester compounds within the scope of this application are selected, the values of F1 and F2 are larger, resulting in a higher number of cycles at 25°C and a smaller cycle expansion rate at 25°C. This indicates good cycle and expansion performance of the secondary battery. This is because non-substituted carboxylic acid ester compounds have lower viscosity. Further introducing non-substituted carboxylic acid ester compounds within the scope of this application into the electrolyte can improve the problem of high viscosity of the compound shown in Formula I, reducing the electrolyte viscosity and improving the wettability of the electrolyte to the positive and negative electrode plates. When there is a local electrolyte deficiency, the nearby electrolyte can quickly replenish the missing portion, thereby enabling the secondary battery to have good cycle and expansion performance.
[0154] The A / B ratio typically affects the cycle performance and expansion performance of secondary batteries. As can be seen from Examples 1-1, 2-1 to 2-9, when the A / B ratio is within the range specified in this application, larger values of F1 and F2 result in a higher number of cycles at 25°C and a lower 25°C cycle expansion rate for the secondary battery. This indicates good cycle performance and expansion performance of the secondary battery.
[0155] Table 3
[0156]
[0157] Note: " / " in Table 3 indicates that there is no corresponding parameter.
[0158] The mass percentages of ethylene carbonate (D%), propylene carbonate (E%), and D+E typically affect the cycle performance and expansion performance of secondary batteries. As seen in Examples 1-1, 3-1 to 3-4, when the electrolyte of the secondary battery includes the compound shown in Formula I, and further introduces ethylene carbonate and / or propylene carbonate, and adjusts their mass percentages (D%), E%), and D+E within the range of this application, the values of F1 and F2 are larger, resulting in a higher number of cycles at 25°C and a smaller cycle expansion rate at 25°C. This indicates good cycle performance and expansion performance of the secondary battery. This is because further introducing ethylene carbonate and / or propylene carbonate into the electrolyte, and adjusting the values of D+E, D, and E within the range of this application, is beneficial for the dissociation of lithium salt in the electrolyte, improving the conductivity of the electrolyte, reducing the polarization of the secondary battery, and also facilitating the formation of lithium salt anions at the positive or negative electrode interface to form inorganic-rich CEI and SEI films, enhancing the interfacial stability between the positive electrode and the electrolyte, and between the negative electrode and the electrolyte, thereby enabling the secondary battery to have good cycle performance and expansion performance.
[0159] The mass percentage (F%) of fluorinated cyclic carbonates typically affects the cycle performance and expansion performance of secondary batteries. As seen in Examples 1-1, 3-5 to 3-9, when the electrolyte of the secondary battery includes the compound shown in Formula I, and further introduces fluorinated cyclic carbonates, and controls its mass percentage (F%) within the scope of this application, the values of F1 and F2 are larger, resulting in a higher number of cycles at 25°C and a smaller cycle expansion rate at 25°C. This indicates good cycle performance and expansion performance of the secondary battery. This is because further introducing fluorinated cyclic carbonates into the electrolyte and controlling the value of F within the scope of this application results in a higher reduction potential for the fluorinated cyclic carbonates, allowing them to preferentially form a film at the negative electrode interface, protecting the negative electrode interface, reducing side reactions between the negative electrode and the electrolyte, and improving the interfacial stability between the negative electrode and the electrolyte. This, in turn, enables the secondary battery to exhibit good cycle performance and expansion performance.
[0160] The type of fluorinated cyclic carbonate typically affects the cycle performance and expansion performance of secondary batteries. As can be seen from Examples 1-1, 3-8, and 3-10, when fluorinated cyclic carbonates within the scope of this application are selected, the values of F1 and F2 are larger, resulting in a higher number of cycles at 25°C and a smaller cycle expansion rate at 25°C. This indicates good cycle and expansion performance of the secondary battery. This is because further introducing fluorinated cyclic carbonates within the scope of this application into the electrolyte results in a higher reduction potential for the fluorinated cyclic carbonates, allowing them to preferentially form a film at the negative electrode interface. This protects the negative electrode interface, reduces side reactions between the negative electrode and the electrolyte, and improves the interfacial stability between the negative electrode and the electrolyte, thereby enabling the secondary battery to exhibit good cycle and expansion performance.
[0161] As can be seen from Examples 1-1 and 3-11 to 3-17, when the electrolyte of the secondary battery includes the compound shown in Formula I, and further introduces at least one of a non-substituted carboxylic acid ester compound, ethylene carbonate, propylene carbonate, or fluorocyclic carbonate, the values of F1 and F2 are larger, and the secondary battery exhibits a greater number of cycles at 25°C and a smaller cycle expansion rate at 25°C. This indicates that the secondary battery has good cycle performance and expansion performance. The compound shown in Formula I has good compatibility and additive properties with the non-substituted carboxylic acid ester compound, ethylene carbonate, propylene carbonate, and fluorocyclic carbonate. The application of the above-mentioned combination of substances in a secondary battery is more conducive to giving the secondary battery good cycle performance and expansion performance.
[0162] Table 4
[0163]
[0164]
[0165] The area ratio of the adhesive layer's orthographic projection onto the surface of the porous substrate layer typically affects the cycle performance and expansion performance of the secondary battery. As can be seen from Examples 1-1, 4-1 to 4-4, when the area ratio of the adhesive layer's orthographic projection onto the surface of the porous substrate layer is within the range of this application, the values of F1 and F2 are larger, resulting in a larger number of cycles at 25°C and a smaller 25°C cycle expansion rate for the secondary battery. This indicates that the secondary battery exhibits good cycle performance and expansion performance.
[0166] The average particle size of polymer particles typically affects the cycle performance and expansion performance of secondary batteries. As can be seen from Examples 1-1, 4-5 to 4-8, when the average particle size of the polymer particles is within the range of this application, the values of F1 and F2 are larger, resulting in a larger number of cycles at 25°C and a smaller expansion rate at 25°C. This indicates that the secondary battery has good cycle performance and expansion performance.
[0167] The type of polymer typically affects the cycle performance and expansion performance of secondary batteries. As can be seen from Examples 1-1 and 4-9, when the polymer type falls within the scope of this application, larger values for F1 and F2 result in a higher number of cycles at 25°C and a lower rate of expansion at 25°C. This indicates good cycle performance and expansion performance of the secondary battery.
[0168] The weight-average molecular weight of a polymer typically affects the cycle performance and expansion performance of a secondary battery. As can be seen from Examples 1-1, 4-10, and 4-11, when the weight-average molecular weight of the polymer is within the range of this application, the values of F1 and F2 are larger, resulting in a larger number of cycles at 25°C and a smaller cycle expansion rate at 25°C. This indicates that the secondary battery exhibits good cycle performance and expansion performance.
[0169] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, or article that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, or article.
[0170] The various embodiments in this specification are described in a related manner. The same or similar parts between the various embodiments can be referred to each other. Each embodiment focuses on describing the differences from other embodiments.
[0171] The above description is only a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of protection of this application.
Claims
1. A secondary battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the electrolyte comprises a compound represented by Formula I. R 11 and R 12 Each is independently selected from C1 to C6 alkyl groups, whether halogenated or unsubstituted, and R 11 Or R 12 At least one of the components is replaced by a halogen; the mass percentage of the compound represented by Formula I is A% based on the mass of the electrolyte, and 30 ≤ A ≤ 80%; The separator includes a porous substrate layer and an adhesive layer disposed on two surfaces of the porous substrate layer. The adhesive layer includes a polymer. The adhesion force between the separator and the positive electrode is F1 N / m, where 10 ≤ F1 ≤ 15. The adhesion force between the separator and the negative electrode is F2 N / m, where 18 ≤ F2 ≤ 25.
2. The secondary battery according to claim 1, wherein it satisfies at least one of the following characteristics: (1)R 11 Or R 12 At least one of them is replaced by F; (2)40≤A≤75。 3. The secondary battery according to claim 1, wherein, The compound represented by Formula I includes at least one of the following compounds:
4. The secondary battery according to any one of claims 1 to 3, wherein, The electrolyte further includes a non-substituted carboxylic acid ester compound, which includes at least one selected from methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, or propyl propionate. Based on the mass of the electrolyte, the mass percentage of the non-substituted carboxylic acid ester compound is B%, 10 ≤ B ≤ 50.
5. The secondary battery according to claim 4, wherein, 1≤A / B≤7.
6. The secondary battery according to any one of claims 1 to 5, wherein it satisfies at least one of the following characteristics: (1) The area ratio of the adhesive layer to the orthographic projection on the surface of the porous substrate layer is 15% to 85%; (2) The average particle size of the polymer particles is 0.2 μm to 2 μm.
7. The secondary battery according to any one of claims 1 to 5, wherein it satisfies at least one of the following characteristics: (1) The area ratio of the adhesive layer to the orthographic projection on the surface of the porous substrate layer is 30% to 70%; (2) The average particle size of the polymer particles is 0.3 μm to 1 μm; (3) The weight-average molecular weight of the polymer is between 300,000 and 3,000,000.
8. The secondary battery according to any one of claims 1 to 7, wherein, The polymer includes non-core-shell polymers or core-shell polymers. The non-core-shell polymer includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, styrene-butadiene copolymer, polyacrylonitrile, butadiene-acrylonitrile copolymer, polyacrylic acid, polyacrylate, or acrylate-styrene copolymer. The core polymer of the core-shell structured polymer includes at least one of polyvinylidene fluoride, polyacrylate, or acrylate-acrylonitrile copolymer, and the shell polymer of the core-shell structured polymer includes at least one of polyvinylidene fluoride-hexafluoropropylene copolymer, styrene-acrylate copolymer, or acrylate-acrylate copolymer.
9. The secondary battery according to any one of claims 1 to 8, wherein, The electrolyte also includes ethylene carbonate and propylene carbonate. Based on the mass of the electrolyte, the mass percentage of ethylene carbonate is D%, the mass percentage of propylene carbonate is E%, 0≤D+E≤10, and 0≤D≤10.
10. The secondary battery according to claim 9, wherein, 0≤E≤10。 11. The secondary battery according to any one of claims 1 to 10, wherein, The electrolyte also includes fluorinated cyclic carbonates, and the mass percentage of the fluorinated cyclic carbonates is F%, based on the mass of the electrolyte, where 1 ≤ F ≤ 20%. The fluorocyclic carbonates include at least one of the following compounds:
12. The secondary battery according to claim 11, wherein, 3≤F≤10。 13. An electronic device comprising a secondary battery as described in any one of claims 1 to 12.
Citation Information
Patent Citations
Electrochemical device and electronic device
CN117276811A
Quick-charging secondary battery and power utilization device
CN117581419A